1973
DOI: 10.1002/ar.1091750205
|View full text |Cite
|
Sign up to set email alerts
|

The ultrastructure of the principal cells and intraepithelial leucocytes in the initial segment of the rat epididymis

Abstract: The ultrastructure of the principal cells and intraepithelial leucocytes in the initial segment of the rat caput epididymidis was examined with the electron microscope. Specializations of the principal cells associated with absorption include numerous endocytic invaginations of the cell surface, numerous coated vesicles and multivesicular bodies in the apical cytoplasm. It was demonstrated that particulate tracers are taken into the cells and sequestered in secondary lysosomes and multivesicular bodies. Morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
79
0
4

Year Published

1976
1976
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(90 citation statements)
references
References 49 publications
7
79
0
4
Order By: Relevance
“…En dépit de la richesse en réticulum endoplasmique lisse des cellules dans certaines espèces la synthèse de stéroïdes dans l'épithélium épididy-maire n'a été démontrée qu'in vitro (Hamilton et Fawcett, 1970). En revanche, la captation de la testostérone par l'épididyme et sa conversion en 5a-dihydrotestostérone ont été mentionnées, en particulier au niveau de la tête (de Larminat et al, 1980 Dym, 1977), le rat (Hoffer et al, 1973) et le hamster (Flickinger et al, 1978), sont considérées comme des lymphocytes intraépithéliaux. Les cellules apicales ont été décrites chez le singe (Ramos et Dym, 1977), les cellules claires chez le hamster (Flickinger et al, 1978 …”
unclassified
“…En dépit de la richesse en réticulum endoplasmique lisse des cellules dans certaines espèces la synthèse de stéroïdes dans l'épithélium épididy-maire n'a été démontrée qu'in vitro (Hamilton et Fawcett, 1970). En revanche, la captation de la testostérone par l'épididyme et sa conversion en 5a-dihydrotestostérone ont été mentionnées, en particulier au niveau de la tête (de Larminat et al, 1980 Dym, 1977), le rat (Hoffer et al, 1973) et le hamster (Flickinger et al, 1978), sont considérées comme des lymphocytes intraépithéliaux. Les cellules apicales ont été décrites chez le singe (Ramos et Dym, 1977), les cellules claires chez le hamster (Flickinger et al, 1978 …”
unclassified
“…Cisternas com aparência vesicular, presentes principalmente nas células principais do epidídimo de paca, e de outros mamíferos 5 , foram identificadas como cisternas dilatadas do RE, que têm poucos ribossomos aderidos 6 , talvez tendo uma possível implicação na secreção de proteínas 18 .…”
Section: Discussionunclassified
“…2,3,4 Aparentemente, proteínas, secretadas pelo RER de células epididimárias, poderiam ser liberadas diretamente no lúmen epididimário. 18 Por outro lado, a secreção de proteínas passaria, diretamente, através do aparelho de Golgi, antes de ser liberada no lúmen tubular. 21 Porém, estudos autoradiográficos, com isótopos marcados, mostraram os grãos de prata inicialmente sobre o RER e sucessivamente sobre o aparelho de Golgi; superfície celular apical e lúmen tubular.…”
Section: Discussionunclassified
“…Hamilton and Robaire & Hermo postulated that these cells secreted of a variety of substances, such as ions, small organic molecules, and glycoproteins,which have been suggested to have a role in sperm maturation. Hoffer et al (1973) and Ramos & Dym have suggested that the principal cells of the mammalian epididymis perform synthesis and secretory activities, based on the presence of numerous rough endoplasmic reticulum lamellae and a well-developed Golgi apparatus.…”
Section: Introductionmentioning
confidence: 99%